2018
DOI: 10.1177/0276236618761371
|View full text |Cite
|
Sign up to set email alerts
|

Imaginary Companions of Blind, Deaf, and Typically Developing School Children

Abstract: Having an imaginary companion (IC) during childhood is associated with developmental advantages. ICs also appear to persist and may serve as a coping mechanism for atrisk children. Few studies have examined imagination in blind and deaf children, two groups who may struggle with peer relationships and loneliness. This study explores the presence of ICs in a sample of 12 blind, 13 deaf, and 26 typically developing, ethnically diverse 8-to 12-year-old children. It examines teacher-and child-reports of competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…(2015) reported evidence that children’s imagination functions, in part, as a cognitive mechanism that allows children to generate new ideas without observing new data. Thus, children with strong fantasy orientations and/or children with imaginary companions, who typically have high levels of fantasy orientation (e.g., Bouldin, 2006; Mathur & Smith, 2008; Smith, 2018), may have advanced cognitive skills that facilitate their ability to engage in early forms of scientific inquiry; that is, inquisitiveness as was assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…(2015) reported evidence that children’s imagination functions, in part, as a cognitive mechanism that allows children to generate new ideas without observing new data. Thus, children with strong fantasy orientations and/or children with imaginary companions, who typically have high levels of fantasy orientation (e.g., Bouldin, 2006; Mathur & Smith, 2008; Smith, 2018), may have advanced cognitive skills that facilitate their ability to engage in early forms of scientific inquiry; that is, inquisitiveness as was assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Imaginative instruction is more than an approach or a technique, it's rather a performance shaper. It worked for deaf and blind learners (Smith, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Imagination worked very well with twelve blind and thirteen deaf culturally varied students. To this end, Smith (2018) investigated the effect of introducing an imaginary friend connected with each student as such groups of students have problems with making social and emotional relations with others and thereby mostly alone. The study reported that more than half of the participants (viz.…”
Section: Introductionmentioning
confidence: 99%
“…Children’s fantasy orientation can predict their levels of affective empathy, potentially due to the fact that children with imaginary companions must hold dual/multiple emotional perspectives and discern between real and pretend emotion (Brown et al, 2017; Niec & Russ, 2002). Children with ICs may also rate themselves as more empathic (Smith, 2019). IC status seems to be associated with more complex, elaborated, and diverse language use as well, implying that ICs could enhance children’s ability to communicate with others (Bouldin et al, 2002; Lin, Zhou, & Wan, et al, 2020; Roby & Kidd, 2008; Singer & Singer, 1992).…”
Section: Theory Of Mindmentioning
confidence: 99%